The Practice of Halal Certification: A Case of Malaysia's Halal Meat-Based Industry - Ainnur Husna Mohd Daud; Umi Hamidaton Mohd Soffian Lee; Anita Ismail (Human Resource Management Academic Research Society, 2024)
Global demand for Halal meat products is expected to grow exponentially, significantly impacting Malaysia's Halal food industry. Halal is an essential part of the Muslim faith. Since the early 2000s, Malaysia has established its procedures and standards to protect consumer interest through Halal certification. Protecting its Muslim consumers' assurance that Halal meat-based products include all elements, processes and Halal certification procedures and practices poses a huge challenge. Therefore, this study discusses the nature practice of Halal certification and its importance in Malaysia's meat-based industry. Library research and document analysis were employed to incorporate detailed ideas by referring to primary and secondary sources such as article journals, official portals, and conference papers. The extracted data were analysed thematically based on the practice, importance, and agencies involved in Halal certification. This study reveals that JAKIM is the key agency in the Halal certification system, attending to the current practice and issues of the Halal certification system in Malaysia. Recommendations based on the research findings suggest that the Malaysian government and JAKIM need to strengthen Halal certification processes and monitoring methods, while the industries must fulfil all requirements that the government has set and provide lawful food for consumers.